Simulation and measurement of air temperatures and mean radiant temperatures in a radiantly heated indoor space. (15th February 2020) - Guo, Hongshan; Ferrara, Maria; Coleman, James; Loyola, Mauricio; Meggers, Forrest
Abstract: Determining variations in air temperature and mean radiant temperature (MRT), two primary environmental parameters directly linked to thermal comfort, can be challenging. The ease and effectiveness of both measurement and simulation are quite different for determining air temperature and MRT. We review these challenges and present an experiment demonstrating how these differences in complexity and resolution can lead to challenges coupling these variables, whose effect on thermal comfort is interdependent. Bearing these challenges in mind, we measured and simulated the air temperatures and MRTs inside a radiantly heated high bay laboratory space. We found the spatial variation of the MRTs to vary by 5 ° C at the elevation of 1.3 m, which is much larger than the variations observed in air temperature. The variations in measured air temperature were up to 2 ° C . This calls for improvement to current tools and methodologies for measuring and simulating the radiant environment, particularly at locations closer to the exterior envelope where hot and cold surfaces affect both air temperature and MRT. It is important to improve the evaluation techniques for MRT, as we observe its spatial variation to be much greater than that of air temperature, while its measurement is limited and usually ignored in practice. Highlights: Simulated and modeled air and mean radiant temperatures distributions. Used angle-factor-based MRT characterization when modeling 3D MRT. Demonstrated rarely-captured spatial MRT variation in an indoor environment. Discussed existing limitations in using Ta to evaluate indoor thermal environment. Showed importance of integral indoor environment sensing and monitoring.